Selectively anchored vanadate host for self-boosting catalytic synthesis of ultra-fine vanadium nitride/nitrogen-doped hierarchical carbon hybrids as superior electrode materials. (1st February 2020) - Yang, Hailun; Ning, Pengge; Cao, Hongbin; Yuan, Menglei; Feng, Jianpeng; Yue, Jiaxin; Liu, Zhenchao; Xu, Gaojie; Li, Yuping
Abstract: Hierarchically nanostructured carbon hybrids with highly exposed active sites and specific surface area have been widely researched in high-performed electrochemical capacitors. Inspired from the synergistic effect of uniformly distributed active components and stable carbon substrate, combining with green solvent extraction process, we explored a facile strategy to prepare vanadium nitride quantum dots/nitrogen-doped hierarchical carbon nanocomposites (VNQD/NDHCs) from vanadium aqueous solution, which can provide large pseudocapacitance and excellent electrochemical stability. Vanadate is selective recovered from aqueous solution in form of vanadium-organic compounds (VAORCs) as precursor. Primary amines favor not only the selective metal-polymer coordination, but also the formation of cross-linked carbon matrix. Then, during chemical molecules vapor deposition (CMVD), the vanadate is in-situ nitrided along with the formation of hierarchical carbon. The prepared VNQD/NDHCs-800 exhibits exceptional capacitance (318.3 F g −1 at 1 A g −1 ) and retains 89.7% of the initial capacities after 12000 cycles. SEM and TEM images confirm that a large amount of quantum dots are well embedded in a graphitic carbon matrix, which provides abundant electroactive sites and fast ion diffusion for capacitive storage. This work indicates that it is feasible to directly recovery valuable metals from aqueous solutions to prepare high-performance electrode materials. Graphical abstract: Image 1 Highlights: Vanadium-based carbon hybrids contain abundant vanadium nitride active sites Vanadium in aqueous solution is almost completely recycled. Scalable fabrication of the products based on green solvent extraction process. The products exhibits exceptional capacitance and excellent cycling stability.